Consequences of protein supplementation on anorexia and expression of immunity in two parasitized sheep breeds - Zaralis K.; Tolkamp B.J.; Houdijk J.G.M.; Kyriazakis I. (Nutritional and foraging ecology of sheep and goats, 2009)
The periparturient breakdown of immunity to parasites has a nutritional basis and it is likely to be associated with host production potential. However, not much is known whether periparturient hosts experience a reduction in food intake (anorexia). Here we investigate: (i) whether parasite infection during the periparturient period results in anorexia and protein supplementation can affect the degree of anorexia in periparturient ewes; and (ii) whether breeds that differ in production potential differ also in the extent of the breakdown of immunity and the degree of anorexia. A 2 × 2 × 2 factorial design was used with two breeds of twin-bearing ewes [Greyface cross, G (n = 32) and Scottish Blackface, B (n = 32)]. Half of the ewes in each breed were trickle infected with 30,000 larvae per week of the abomasal parasite Teladorsagia circumcincta, while the other half was not infected. In addition, half of the ewes in each infection treatment in each breed were fed either a high or a low protein diet. Infection with T. circumcincta resulted in breakdown of immunity and in a reduction in food intake in both breeds. The study has shown that breeds can differ in the extent of the breakdown of immunity, but these breed differences were not associated with a significant difference in the degree of anorexia. The results showed that protein supplementation can assist periparturient ewes in reducing the breakdown of immunity, but protein supplementation did not significantly affect the degree of anorexia.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)